Environment-friendly BOPP laser transfer film and preparation method thereof
By using aqueous polyurethane emulsion and aqueous acrylic resin as the substrate in the laser transfer film, combined with PEG grafting and linseed oil modification treatment, the environmental pollution problem caused by organic volatile solvents in the existing laser transfer film is solved, and the preparation of the environmentally friendly BOPP laser transfer film is realized, with excellent environmental protection and use performance.
Patent Information
- Application Number
- CN202411659210.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
AI Technical Summary
The existing laser transfer film contains a large number of organic volatile solvents such as alcohols, esters, ketones, etc., which leads to the generation of VOCs, pollutes the environment and is difficult to meet the requirements of food packaging.
The environmentally friendly BOPP laser transfer film was prepared by using aqueous polyurethane emulsion and aqueous acrylic resin as the substrate for laser molding coatings, combined with PEG grafting technology and linseed oil modification treatment.
Through the combination of water-based polyurethane and aqueous acrylic resin, the environmental protection of the coating is improved, the generation of VOCs is reduced, the integrity and anti-adhesion of the laser molded layer are improved, and the service life of the transfer film is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of transfer films, and more specifically, to an environmentally friendly BOPP laser transfer film and a preparation method thereof. Background Art
[0002] Laser packaging materials are various packaging and decorative materials produced using laser holographic technology. Since they were put on the market, their applications in food, medicine, daily chemicals, tobacco and alcohol have been rapidly promoted, becoming a cutting-edge product in the world's printing and packaging industry.
[0003] The current laser transfer film mainly uses BOPP (biaxially oriented polypropylene film) and PET (polyethylene terephthalate plastic) as the base film, and transparent synthetic resin as the laser transfer coating. The current laser transfer coating contains a large amount of organic volatile solvents such as alcohols, esters, and ketones, which are more likely to produce VOCs, causing pollution to the production environment and the atmospheric environment, and it is difficult to meet the requirements of food packaging. Therefore, it is necessary to improve the transfer film. Summary of the invention
[0004] In order to improve the environmental friendliness of the transfer film, the present application provides an environmentally friendly BOPP laser transfer film and a preparation method thereof, which adopts the following technical solutions:
[0005] In a first aspect, the present application provides an environmentally friendly BOPP laser transfer film, comprising a BOPP base film, a laser molding layer and an aluminum plating layer arranged in sequence;
[0006] Wherein, the laser molding layer is composed of molding coating, and the molding coating includes the following raw materials in parts by weight:
[0007] 60-80 parts of waterborne polyurethane emulsion;
[0008] 5-15 parts of water-based acrylic resin;
[0009] 5-10 parts of filler;
[0010] 1-3 parts of additives;
[0011] 30-40 parts water;
[0012] The aqueous polyurethane emulsion is an aqueous polyurethane emulsion grafted with PEG.
[0013] By adopting the above technical scheme, the present application preferably uses water-based polyurethane emulsion and water-based acrylic resin as the base material of the coating, and the solvent is water, which improves the phenomenon of solvent volatilization to produce VOCs, reduces the harm of the coating to the environment and human body, and stably improves the environmental protection of the coating.
[0014] Waterborne polyurethane emulsion is used as the base material of the coating. Waterborne polyurethane has the advantages of good film-forming property, high temperature resistance and easy peeling. Waterborne acrylic resin has good leveling property. By combining waterborne polyurethane with waterborne acrylic resin, a coating with excellent temperature resistance, excellent moldability and excellent leveling effect can be obtained, which is beneficial to improve the integrity of the laser molding layer.
[0015] By grafting PEG onto waterborne polyurethane, PEG can effectively reduce the surface energy of the material surface, that is, it can effectively improve the anti-stickiness of the coating. PEG has better non-toxicity and biocompatibility, is not easy to stick to the plate during the molding process, forms a clear molded laser layer, and still has better environmental protection.
[0016] Optionally, the waterborne polyurethane is grafted with linseed oil-based PEG.
[0017] By adopting the above technical solution, linseed oil-based PEG is used to graft waterborne polyurethane. Since the mobility of PEG is limited after being grafted on waterborne polyurethane, PEG can be modified by linseed oil to graft side chain ether bond coupling groups with excellent mobility on PEG, which can effectively improve the mobility of PEG, thereby enabling the coating to obtain excellent anti-stickiness and anti-fouling properties, and obtain a long-lasting and clear laser molding layer. In addition, linseed oil is abundant in resources, green and renewable, has better biosafety and degradation performance, and further improves the environmental protection of the transfer film.
[0018] Optionally, the linseed oil-based PEG is prepared as follows: an excess of MPEG500 is added to a container, epoxy linseed oil is added to the container at 65° C. using tetrafluoroboric acid as a catalyst, the reaction product is dissolved in a small amount of ethyl acetate, a large amount of saturated brine is added to extract and purify, after purification, it is dried over anhydrous magnesium sulfate, filtered and rotary evaporated to obtain linseed oil-based PEG.
[0019] Optionally, in the preparation of the linseed oil-based PEG, the molar ratio of hydroxyl group to epoxy group is 1.5-2:1.
[0020] By adopting the above technical solution, the molar ratio of hydroxyl group to epoxy group is optimized. Under the appropriate molar ratio, MPEG500 can fully open the ring of epoxy linseed oil, so that the epoxy linseed oil and PEG are fully grafted.
[0021] Optionally, the preparation of the epoxy linseed oil is as follows: linseed oil and formic acid are added to a container, heated, hydrogen peroxide and sulfuric acid are added, the reaction is continued, the reaction is terminated, the temperature is lowered, separation is performed, the oil layer is retained, the oil layer is neutralized, the reduced pressure is used for deacidification, the temperature is lowered, and filtering is performed to obtain the epoxy linseed oil; wherein the mass ratio of linseed oil, formic acid, hydrogen peroxide and sulfuric acid is 1:0.06:0.001-0.0015:0.65.
[0022] By adopting the above technical scheme, the preparation method of epoxy linseed oil is optimized and the proportion of each component in the preparation process of epoxy linseed oil is optimized. Under the appropriate ratio, epoxy linseed oil with suitable epoxy value can be obtained, and the post-treatment process is simple. Sulfuric acid is preferably used to catalyze the epoxy linseed oil, which has better catalytic activity, low cost and is easily available.
[0023] Optionally, the filler includes silicon dioxide, calcium phosphate and mica powder.
[0024] By adopting the above technical scheme, the surface of silicon dioxide has highly active silanol groups, and then a cross-linked network structure can be constructed between silicon dioxide particles to form a unique three-dimensional structure, thereby effectively improving the compression resistance and strength of the molded coating. The active hydroxyl groups in the mica powder can interact with the molecular chain structure of polyurethane to obtain a higher interaction force inside the coating and improve the strength of the molded coating. The unique lamellar structure of the mica powder gives it a lower surface energy. After being added to the coating, the surface energy of the molded coating can be effectively reduced, further improving the anti-sticking effect of the molded coating. It is preferred to use silicon dioxide and mica powder as fillers, so that the coating obtains excellent peeling effect, compression resistance, strength, while obtaining better anti-sticking and antistatic effects.
[0025] Optionally, the mica powder is prepared as follows: the mica powder is dispersed in a nitric acid solution, stirred, washed with water, and dried to obtain acidified mica powder; the acidified mica powder is dispersed in a sodium chloride solution, filtered, and dried to obtain an intermediate powder; the intermediate powder is mixed with CTAB, filtered, and dried to obtain intercalated mica powder; the intercalated mica powder is dispersed in ethanol, centrifuged and dried to obtain exfoliated sheets; the exfoliated sheets are mixed with PEI, filtered, washed, and dried to obtain modified mica powder.
[0026] By adopting the above technical solution, mica powder is modified by acidification, intercalation and PEI, so that the surface of mica powder flakes can carry electric charge and form three smaller flake structures in the coating. The flake structure can effectively hinder the penetration of corrosive media and promote the film formation of the coating, thereby improving the corrosion resistance and film forming properties of the coating. At the same time, the modified mica powder can obtain excellent self-lubricating effect, thereby improving the wear and scratch resistance of the molded coating and extending the service life of the transfer film.
[0027] Optionally, the silicon dioxide and calcium phosphate are respectively modified by polyethylene wax.
[0028] By adopting the above technical scheme, polyethylene wax is used to modify silicon dioxide or calcium phosphate. The polyethylene wax has a lower polarity and can reduce the possibility of agglomeration between silicon dioxide or calcium phosphate particles, so that the silicon dioxide or calcium phosphate is evenly dispersed in the molded coating, so that the molded coating obtains uniform strength and wear resistance, and reduces the surface polarity of the molded coating, improves the anti-stick effect of the molded coating, and is conducive to forming a clear molded coating.
[0029] Optionally, the polyethylene wax is prepared as follows: MAH-polyethylene wax, calcium phosphate, sodium hydroxide and water are reacted at high temperature and mechanically stirred to obtain a polyethylene wax emulsion.
[0030] By adopting the above technical scheme, in the prepared polyethylene wax emulsion, calcium phosphate can be grafted on the surface of the polyethylene wax, thereby forming an organic-inorganic cross-linked network, further reducing the agglomeration between calcium phosphate particles, enhancing the bonding strength between the polyethylene wax and the polyurethane, further improving the strength of the molded coating as well as the wear resistance and scratch resistance, and effectively extending the service life of the molded coating.
[0031] In a second aspect, the present application provides a method for preparing an environmentally friendly BOPP laser transfer film, using the following technical solution:
[0032] A method for preparing an environmentally friendly BOPP laser transfer film comprises the following steps:
[0033] S1. Preparation of molding coating: Weigh water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water respectively by weight, stir and mix to obtain molding coating;
[0034] S2. Preparation of transfer film: coating a molding coating on a BOPP base film, drying and curing to obtain a coating, molding on the coating, hot stamping the laser information on the molding plate onto the coating, vacuum aluminum plating to obtain a transfer film.
[0035] In summary, this application has the following beneficial effects:
[0036] 1. Since the present application preferably uses water-based polyurethane emulsion and water-based acrylic resin as the base material of the coating, the solvent is water, which improves the phenomenon of solvent volatilization to produce VOCs, and obtains an environmentally friendly coating. By combining water-based polyurethane and water-based acrylic resin, a coating with excellent temperature resistance, excellent moldability, and excellent leveling effect can be obtained, which is beneficial to improving the integrity of the laser molding layer. By grafting water-based polyurethane with PEG, PEG can effectively reduce the surface energy of the material surface, that is, it can effectively improve the anti-stickiness of the coating, and it is not easy to stick to the plate during the molding process, forming a clear molded laser layer, and still has better environmental protection.
[0037] 2. In the present application, PEG is modified by linseed oil, and side chain ether bond coupling groups with excellent mobility can be grafted onto PEG, which can effectively improve the mobility of PEG, thereby enabling the coating to obtain excellent anti-stickiness and anti-fouling properties, and obtaining a durable and clear laser molded layer.
[0038] 3. The present application uses acidification, intercalation and PEI to modify mica powder, which can make the surface of mica powder flakes carry electric charge and form three smaller flake structures in the coating. The flake structure can effectively hinder the penetration of corrosive media and promote the film formation of the coating, thereby improving the corrosion resistance and film forming properties of the coating. At the same time, the modified mica powder can obtain the self-lubricating effect of Unicon, thereby improving the wear and scratch resistance of the molded coating and extending the service life of the transfer film. DETAILED DESCRIPTION
[0039] The present application is further described in detail below with reference to the embodiments.
[0040] Preparation Example
[0041] Preparation Example of Epoxidized Linseed Oil
[0042] Preparation Example 1
[0043] Add linseed oil and formic acid into a container, start stirring, and slowly heat in a water bath. When the temperature rises to 55°C, slowly drip a mixed solution of hydrogen peroxide and 95% sulfuric acid by mass, and complete the dripping in 1 hour. Continue the reaction at 70°C; after the reaction is completed, cool down. Pour the product into a separatory funnel, let it stand, and remove the water layer. Neutralize the oil layer with a mass fraction of 4% sodium hydroxide solution to a pH value of about 9. Then deacidify under reduced pressure, cool down, and filter to obtain epoxy linseed oil.
[0044] Among them, the mass ratio of linseed oil, formic acid, hydrogen peroxide and sulfuric acid is 1:0.06:0.001:0.65.
[0045] Preparation Example 2
[0046] Add linseed oil and formic acid into a container, start stirring, and slowly heat in a water bath. When the temperature rises to 55°C, slowly drip a mixed solution of hydrogen peroxide and 95% sulfuric acid by mass, and complete the dripping in 1 hour. Continue the reaction at 70°C; after the reaction is completed, cool down. Pour the product into a separatory funnel, let it stand, and remove the water layer. Neutralize the oil layer with a mass fraction of 4% sodium hydroxide solution to a pH value of about 9. Then deacidify under reduced pressure, cool down, and filter to obtain epoxy linseed oil.
[0047] Among them, the mass ratio of linseed oil, formic acid, hydrogen peroxide and sulfuric acid is 1:0.06:0.0015:0.65.
[0048] Preparation Example of Linseed Oil-Based PEG
[0049] Preparation Example 3
[0050] An excess of MPEG500 was added to a three-necked round-bottom flask, and dripped dropwise into the epoxy linseed oil prepared in Preparation Example 1 under the catalysis of 0.2% tetrafluoroboric acid and a constant temperature oil bath at 65°C. The reaction was continued for 15 minutes, and the reaction product was dissolved in a small amount of ethyl acetate, and extracted and purified by adding a large amount of saturated brine. After purification, it was dried over anhydrous magnesium sulfate, filtered and rotary evaporated to obtain a purified product. Among them, the molar ratio of hydroxyl group to epoxy group was 1.5:1.
[0051] Preparation Example 4
[0052] An excess of MPEG500 was added to a three-necked round-bottom flask, and dripped dropwise into the epoxy linseed oil prepared in Preparation Example 1 under the catalysis of 0.2% tetrafluoroboric acid and a constant temperature oil bath at 65°C. The reaction was continued for 15 minutes, and the reaction product was dissolved in a small amount of ethyl acetate, and extracted and purified by adding a large amount of saturated brine. After purification, it was dried over anhydrous magnesium sulfate, filtered and rotary evaporated to obtain a purified product. The molar ratio of hydroxyl group to epoxy group was 2:1.
[0053] Preparation Example 5
[0054] An excess of MPEG500 was added to a three-necked round-bottom flask, and dripped dropwise into the epoxy linseed oil prepared in Preparation Example 2 under the catalysis of 0.2% tetrafluoroboric acid and a constant temperature oil bath at 65°C. The reaction was continued for 15 minutes, and the reaction product was dissolved in a small amount of ethyl acetate, and extracted and purified by adding a large amount of saturated brine. After purification, it was dried over anhydrous magnesium sulfate, filtered and rotary evaporated to obtain a purified product. The molar ratio of hydroxyl group to epoxy group was 2:1.
[0055] Mica powder preparation example
[0056] Preparation Example 6
[0057] Heat the mica powder to 800°C, cool it, disperse 15g of the mica powder in 500mL of a 5% nitric acid solution, stir it, wash it with water, and dry it to obtain acidified mica powder; disperse the acidified mica powder in a sodium chloride solution, filter it, and dry it at 80°C to obtain an intermediate powder; mix the intermediate powder with CTAB in a mass ratio of 15:46, disperse it in deionized water, stir it for 24h, filter it, and dry it to obtain intercalated mica powder; disperse the intercalated mica powder in ethanol, stir it, and centrifuge it to obtain an exfoliated layer; dissolve 5g of the exfoliated layer, 100mg of PEI and 292mg of sodium chloride in 500mL of deionized water, mix it, stir it for 1h, filter it, wash it, and dry it to obtain a modified mica powder.
[0058] Preparation example of polyethylene wax modified silica
[0059] Preparation Example 7
[0060] The polyethylene wax and nano silicon dioxide are stirred and mixed at a solid-liquid ratio of 1:10, filtered, and dried to obtain modified silicon dioxide.
[0061] Preparation example of polyethylene wax modified calcium phosphate
[0062] Preparation Example 8
[0063] Disperse 4.44 g of dihydrate and calcium chloride in 474 mL of anhydrous ethanol, stir magnetically for 30 min to obtain a mixed solution, add 61.152 mL of triethylamine to the mixed solution, continue stirring for 10 min, add ethanolic phosphoric acid solution (2.64 g of phosphoric acid + 23 mL of ethanol), stir at room temperature for 12 h, centrifuge, retain the solid, wash, and dry to obtain calcium phosphate.
[0064] MAH-polyethylene wax, calcium phosphate, sodium hydroxide and water were reacted at 145° C. for 60 minutes and mechanically stirred at 900 r / min to obtain a polyethylene wax emulsion.
[0065] The molar ratio of sodium hydroxide to MAH-polyethylene wax is 2:1, and the added amount of calcium phosphate is 10%.
[0066] Example
[0067] Example 1
[0068] On the one hand, the present application provides an environmentally friendly BOPP laser transfer film, comprising a BOPP base film, a laser molding layer and an aluminum plating layer arranged in sequence;
[0069] Among them, the laser molding layer is composed of molding coating, and the molding coating includes the following raw materials in parts by weight: water-based polyurethane emulsion, water-based acrylic resin, filler, additives and water. The specific mass is shown in the table below.
[0070] The filler includes nano silicon dioxide, calcium phosphate and mica powder in a mass ratio of 2:2:1. The additives include rheological additive (BYK-350), wetting agent (DiGao KL245) and defoaming agent (BYK-019) in equal amounts.
[0071] The waterborne polyurethane is a waterborne polyurethane modified by PEG. The preparation of the waterborne polyurethane is as follows:
[0072] IPDI, PEG and DMPA were mixed and dispersed uniformly at a molar ratio of 1.85:0.84:1 at 78°C, prepolymerized for 10 minutes, and then DBTDL catalyst (18 μL) was added to react for 1-2 hours until the viscosity of the prepolymer increased, and then butanone (40% solid content) was added to dilute it and continue to react for 1-2 hours. After the reaction was completed, it was cooled to room temperature, and a certain proportion of triethylamine (neutralization degree 97%) was added for neutralization. After neutralization for 30 minutes, a certain amount of deionized water (15% solid content) was added and emulsified for 2 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a modified waterborne polyurethane emulsion.
[0073] On the other hand, the present application provides a method for preparing an environmentally friendly BOPP laser transfer film, comprising the following steps:
[0074] S1. Preparation of molding coating: Weigh water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water respectively by weight, stir and mix to obtain molding coating;
[0075] S2. Preparation of transfer film: coating a molding coating on a BOPP base film, drying and curing to obtain a coating, molding on the coating, hot stamping the laser information on the molding plate onto the coating, vacuum aluminum plating to obtain a transfer film.
[0076] Table 1 Composition of molding coatings in Examples 1-3
[0077] Weight / kg Example 1 Example 2 Example 3 Waterborne polyurethane emulsion 60 70 80 Water-based acrylic resin 5 10 15 filler 5 8 10 Additives 1 2 3 water 30 35 40
[0078] Example 2
[0079] On the one hand, the present application provides an environmentally friendly BOPP laser transfer film, comprising a BOPP base film, a laser molding layer and an aluminum plating layer arranged in sequence;
[0080] Wherein, the laser molding layer is composed of molding coating, and the molding coating includes the following raw materials in parts by weight: water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water. The specific mass is shown in Table 1.
[0081] The filler includes nano silicon dioxide, calcium phosphate and mica powder in a mass ratio of 2:2:1. The additives include rheological additive (BYK-350), wetting agent (DiGao KL245) and defoaming agent (BYK-019) in equal amounts.
[0082] The waterborne polyurethane is a waterborne polyurethane modified by PEG. The preparation of the waterborne polyurethane is as follows:
[0083] IPDI, PEG and DMPA were mixed and dispersed uniformly at a molar ratio of 1.85:0.84:1 at 78°C, prepolymerized for 10 minutes, and then DBTDL catalyst (18 μL) was added to react for 1-2 hours until the viscosity of the prepolymer increased, and then butanone (40% solid content) was added to dilute it and continue to react for 1-2 hours. After the reaction was completed, it was cooled to room temperature, and a certain proportion of triethylamine (neutralization degree 97%) was added for neutralization. After neutralization for 30 minutes, a certain amount of deionized water (15% solid content) was added and emulsified for 2 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a modified waterborne polyurethane emulsion.
[0084] On the other hand, the present application provides a method for preparing an environmentally friendly BOPP laser transfer film, comprising the following steps:
[0085] S1. Preparation of molding coating: Weigh water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water respectively by weight, stir and mix to obtain molding coating;
[0086] S2. Preparation of transfer film: coating a molding coating on a BOPP base film, drying and curing to obtain a coating, molding on the coating, hot stamping the laser information on the molding plate onto the coating, vacuum aluminum plating to obtain a transfer film.
[0087] Example 3
[0088] On the one hand, the present application provides an environmentally friendly BOPP laser transfer film, comprising a BOPP base film, a laser molding layer and an aluminum plating layer arranged in sequence;
[0089] Wherein, the laser molding layer is composed of molding coating, and the molding coating includes the following raw materials in parts by weight: water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water. The specific mass is shown in Table 1.
[0090] The filler includes nano silicon dioxide, calcium phosphate and mica powder in a mass ratio of 2:2:1. The additives include rheological additive (BYK-350), wetting agent (DiGao KL245) and defoaming agent (BYK-019) in equal amounts.
[0091] The waterborne polyurethane is a waterborne polyurethane modified by PEI. The preparation of the waterborne polyurethane is as follows:
[0092] IPDI, PEG and DMPA were mixed and dispersed uniformly at a molar ratio of 1.85:0.84:1 at 78°C, prepolymerized for 10 minutes, and then DBTDL catalyst (18 μL) was added to react for 1-2 hours until the viscosity of the prepolymer increased, and then butanone (40% solid content) was added to dilute it and continue to react for 1-2 hours. After the reaction was completed, it was cooled to room temperature, and a certain proportion of triethylamine (neutralization degree 97%) was added for neutralization. After neutralization for 30 minutes, a certain amount of deionized water (15% solid content) was added and emulsified for 2 hours. After the reaction was completed, the solvent was removed by rotary evaporation to obtain a modified waterborne polyurethane emulsion.
[0093] On the other hand, the present application provides a method for preparing an environmentally friendly BOPP laser transfer film, comprising the following steps:
[0094] S1. Preparation of molding coating: Weigh water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water respectively by weight, stir and mix to obtain molding coating;
[0095] S2. Preparation of transfer film: coating a molding coating on a BOPP base film, drying and curing to obtain a coating, molding on the coating, hot stamping the laser information on the molding plate onto the coating, vacuum aluminum plating to obtain a transfer film.
[0096] Example 4
[0097] The difference from Example 2 is that the waterborne polyurethane is a waterborne polyurethane modified by linseed oil-based PEG, and the preparation of the waterborne polyurethane is as follows:
[0098] IPDI, the linseed oil-based PEG prepared in Preparation Example 3 and DMPA were mixed and dispersed uniformly at a molar ratio of 1.85:0.84:1 at 78° C., prepolymerized for 10 minutes, and then DBTDL catalyst (18 μL) was added to react for 1-2 hours until the viscosity of the prepolymer increased, then butanone (40% solid content) was added for dilution, and the reaction was continued for 1-2 hours. After the reaction was completed, it was cooled to room temperature, and a certain proportion of triethylamine (neutralization degree 97%) was added for neutralization. After neutralization for 30 minutes, a certain amount of deionized water (15% solid content) was added for emulsification for 2 hours. After the end, the solvent was removed by rotary evaporation to obtain a modified waterborne polyurethane emulsion.
[0099] Example 5
[0100] The difference from Example 2 is that the waterborne polyurethane is a waterborne polyurethane modified by linseed oil-based PEG, and the preparation of the waterborne polyurethane is as follows:
[0101] IPDI, the linseed oil-based PEG prepared in Preparation Example 4 and DMPA were mixed and dispersed uniformly at a molar ratio of 1.85:0.84:1 at 78° C., prepolymerized for 10 minutes, and then DBTDL catalyst (18 μL) was added to react for 1-2 hours until the viscosity of the prepolymer increased, and then butanone (40% solid content) was added for dilution, and the reaction was continued for 1-2 hours. After the reaction was completed, it was cooled to room temperature, and a certain proportion of triethylamine (neutralization degree 97%) was added for neutralization. After neutralization for 30 minutes, a certain amount of deionized water (15% solid content) was added and emulsified for 2 hours. After the end, the solvent was removed by rotary evaporation to obtain a modified waterborne polyurethane emulsion.
[0102] Example 6
[0103] The difference from Example 2 is that the waterborne polyurethane is a waterborne polyurethane modified by linseed oil-based PEG, and the preparation of the waterborne polyurethane is as follows:
[0104] IPDI, the linseed oil-based PEG prepared in Preparation Example 5 and DMPA were mixed and dispersed uniformly at a molar ratio of 1.85:0.84:1 at 78° C., prepolymerized for 10 minutes, and then DBTDL catalyst (18 μL) was added to react for 1-2 hours until the viscosity of the prepolymer increased, and then butanone (40% solid content) was added for dilution, and the reaction was continued for 1-2 hours. After the reaction was completed, it was cooled to room temperature, and a certain proportion of triethylamine (neutralization degree 97%) was added for neutralization. After neutralization for 30 minutes, a certain amount of deionized water (15% solid content) was added and emulsified for 2 hours. After the end, the solvent was removed by rotary evaporation to obtain a modified waterborne polyurethane emulsion.
[0105] Example 7
[0106] The difference from Example 2 is that the filler includes nano-silicon dioxide, calcium phosphate and the modified mica powder prepared in Preparation Example 6 in a mass ratio of 2:2:1.
[0107] Example 8
[0108] The difference from Example 2 is that the filler includes the modified nano-silicon dioxide, calcium phosphate and mica powder prepared in Preparation Example 7 in a mass ratio of 2:2:1.
[0109] Example 9
[0110] The difference from Example 2 is that the filler includes nano-silicon dioxide, the calcium phosphate prepared in Preparation Example 8, and mica powder in a mass ratio of 2:2:1.
[0111] Example 10
[0112] The difference from Example 2 is that the filler includes the modified nano-silicon dioxide prepared in Preparation Example 7, the calcium phosphate prepared in Preparation Example 8 and the modified mica powder prepared in Preparation Example 6 in a mass ratio of 2:2:1.
[0113] Comparative Example
[0114] Comparative Example 1
[0115] The difference between this comparative example and Example 2 is that the aqueous polyurethane emulsion in this comparative example is not modified.
[0116] Comparative Example 2
[0117] The difference between this comparative example and Example 2 is that no water-based acrylic resin is added in this comparative example.
[0118] Performance testing
[0119] (1) Anti-sticking performance test: The molded coating is made into a sample of 2 cm × 2 cm in size, and a pressure of 3 kg / cm2 is applied. The sample is placed in a 50°C oven for 24 hours to observe the surface embossing effect. The embossing area and degree are rated as 1 to 5. The sample with basically no damage or only slight embossing is rated as 5.
[0120] (2) Thermal adhesion test: A soldering iron at a certain temperature is placed in contact with the front side of a folded paper for a certain period of time and then separated. After the paper cools down, observe whether there is adhesion or whitening between the folded part and the front side of the paper.
[0121] (3) Wear resistance test: According to the national standard "GB1768-(79)88 Test Method for Wear Resistance of Paint Film", a JM-1 paint film wear tester is used. After a certain number of rotations, the weight loss of the molded coating is used to indicate its wear resistance.
[0122] (4) Adhesion test: The adhesion effect of the molded coating is measured by the circle method.
[0123] Table 2 Performance test
[0124]
[0125] Through the thermal adhesion test, the thermal adhesion performance of the molded coating in Example 2 is better, while the thermal adhesion performance of the molded coating in Comparative Example 1 is poor.
[0126] The corresponding working curve was established with reference to YC / T 207-2014, and the headspace separation-gas chromatography method was used for testing. After testing, the VOCs of the molded coating prepared in Examples 1-10 was ≤1.3mg / m 2 .
[0127] Use 3M tape to quickly peel off at a 45° angle, and the peeling should be clean without residual adhesive. After the peeling performance test, the peeling performance of the molded coatings in Examples 1-10 can reach the qualified state of clean peeling without residual adhesive.
[0128] Combining the performance test comparison in Table 2, we can find that:
[0129] 1. By comparing Examples 1-3 with Comparative Examples 1-2, it can be found that the wear resistance, anti-sticking performance and adhesion of the molded coatings prepared in Examples 1-3 are all improved, which shows that in this application, by combining water-based polyurethane with water-based acrylic resin, a coating with excellent temperature resistance, excellent moldability and excellent leveling effect can be obtained, which is beneficial to improving the integrity of the laser molded layer. By using PEG grafted water-based polyurethane, PEG can effectively reduce the surface energy of the material surface, that is, it can effectively improve the anti-sticking property of the coating, form a clear molded laser layer, and still have better environmental protection.
[0130] 2. By comparing Examples 4-5 with Example 2, it can be found that the wear resistance, anti-sticking performance and adhesion of the molded coatings prepared in Examples 4-5 are improved. This shows that in the present application, linseed oil-based PEG is used to graft waterborne polyurethane. Since the mobility of PEG is limited after being grafted on the waterborne polyurethane, the PEG is modified by linseed oil, and side chain ether bond coupling groups with excellent mobility can be grafted on the PEG, which can effectively improve the mobility of PEG, thereby enabling the coating to obtain excellent anti-sticking and anti-fouling properties, and obtain a durable and clear laser molded layer.
[0131] 3. By comparing Examples 5-6 with Example 2, it can be found that the wear resistance, anti-sticking performance and adhesion of the molded coatings prepared in Examples 5-6 are improved, which means that the molar ratio of hydroxyl to epoxy groups is optimized in the present application. Under the appropriate molar ratio, MPEG500 can fully open the ring of epoxy linseed oil, so that the epoxy linseed oil and PEG are fully grafted.
[0132] 4. By comparing Example 7 with Example 2, it can be found that the wear resistance, anti-sticking performance and adhesion of the molded coating prepared in Example 7 are improved, which means that the mica powder is modified by acidification, intercalation and PEI in the present application, which can make the surface of the mica powder flakes carry charges and form three layers of smaller flake structures in the coating. The flake structure can effectively hinder the penetration of corrosive media, promote the film formation of the coating, and improve the corrosion resistance and film forming properties of the coating.
[0133] 5. By comparing Example 8 with Example 2, it can be found that the wear resistance, anti-sticking performance and adhesion of the molded coating prepared in Example 8 are improved, which shows that the polyethylene wax in this application has a lower polarity, which can reduce the possibility of agglomeration between silica particles, so that silica is evenly dispersed in the molded coating, so that the molded coating obtains uniform strength and wear resistance.
[0134] 6. By comparing Examples 9-10 with Example 2, it can be found that the wear resistance, anti-sticking performance and adhesion of the molded coatings prepared in Examples 9-10 are improved, which means that calcium phosphate can be grafted onto the surface of polyethylene wax in the present application to form an organic-inorganic cross-linked network, further reducing the agglomeration between calcium phosphate particles, enhancing the bonding strength between polyethylene wax and polyurethane, further improving the strength of the molded coating as well as the wear resistance and scratch resistance, and effectively extending the service life of the molded coating.
[0135] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An environmentally friendly BOPP laser transfer film, characterized in that: It includes a BOPP base film, a laser molding layer and an aluminum plating layer which are arranged in sequence; Wherein, the laser molding layer is composed of molding coating, and the molding coating includes the following raw materials in parts by weight: 60-80 parts of waterborne polyurethane emulsion; 5-15 parts of water-based acrylic resin; 5-10 parts of filler; 1-3 parts of additives; 30-40 parts water; The aqueous polyurethane emulsion is an aqueous polyurethane emulsion grafted with PEG.
2. The environmentally friendly BOPP laser transfer film according to claim 1, characterized in that: The waterborne polyurethane is grafted with linseed oil-based PEG.
3. The environmentally friendly BOPP laser transfer film according to claim 2, characterized in that: The linseed oil-based PEG is prepared as follows: an excess of MPEG500 is added to a container, and epoxy linseed oil is added to the container at 65° C. using tetrafluoroboric acid as a catalyst, the reaction product is dissolved in a small amount of ethyl acetate, and a large amount of saturated saline is added for extraction and purification. After purification, the linseed oil-based PEG is dried over anhydrous magnesium sulfate, filtered and rotary evaporated to obtain the linseed oil-based PEG.
4. The environmentally friendly BOPP laser transfer film according to claim 3, characterized in that: In the preparation of the linseed oil-based PEG, the molar ratio of hydroxyl group to epoxy group is 1.5-2:
1.
5. The environmentally friendly BOPP laser transfer film according to claim 3, characterized in that: The preparation of the epoxy linseed oil is as follows: adding linseed oil and formic acid into a container, heating, adding hydrogen peroxide and sulfuric acid, continuing the reaction, cooling after the reaction is finished, separating, retaining the oil layer, neutralizing the oil layer, deacidifying under reduced pressure, cooling, filtering, and obtaining the epoxy linseed oil; wherein the mass ratio of linseed oil, formic acid, hydrogen peroxide and sulfuric acid is 1:0.06:0.001-0.0015:0.
65.
6. The environmentally friendly BOPP laser transfer film according to claim 1, characterized in that: The filler includes silicon dioxide, calcium phosphate and mica powder.
7. The environmentally friendly BOPP laser transfer film according to claim 6, characterized in that: The mica powder is prepared as follows: the mica powder is dispersed in a nitric acid solution, stirred, washed with water, and dried to obtain acidified mica powder; the acidified mica powder is dispersed in a sodium chloride solution, filtered, and dried to obtain an intermediate powder; the intermediate powder is mixed with CTAB, filtered, and dried to obtain an intercalated mica powder; the intercalated mica powder is dispersed in ethanol, centrifuged, and dried to obtain an exfoliated layer; the exfoliated layer is mixed with PEI, filtered, washed, and dried to obtain a modified mica powder.
8. The environmentally friendly BOPP laser transfer film according to claim 6, characterized in that: The silicon dioxide and calcium phosphate are respectively modified by polyethylene wax.
9. The environmentally friendly BOPP laser transfer film according to claim 8, characterized in that: The polyethylene wax modified calcium phosphate is prepared as follows: MAH-polyethylene wax, calcium phosphate, sodium hydroxide and water are reacted at high temperature and mechanically stirred to obtain polyethylene wax emulsion.
10. The method for preparing an environmentally friendly BOPP laser transfer film according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Preparation of molding coating: Weigh water-based polyurethane emulsion, water-based acrylic resin, filler, additive and water respectively by weight, stir and mix to obtain molding coating; S2. Preparation of transfer film: coating a molding coating on a BOPP base film, drying and curing to obtain a coating, molding on the coating, hot stamping the laser information on the molding plate onto the coating, vacuum aluminum plating to obtain a transfer film.
Citation Information
Patent Citations
Aqueous-transfer direct-plated laser coating material for cigarette packets and preparation method
CN107266986A
Vegetable oil-based antifouling polyol, preparation method and application thereof
CN113372548A
Environment-friendly BOPP laser transfer film
CN116587760A
Preparation method of ultrahigh wear-resistant self-emulsifying polyethylene wax emulsion
CN116769184A
Method for in-situ reinforcement of PVB (polyvinyl butyral) film material by surface modification of nano mica and product
CN117362713A
Cited By
Environment-friendly transfer film and preparation method thereof
CN121930529A